A study on machinability aspects and parametric optimization of Inconel 825 using Rao1, Rao2, Rao3 approach. (2021) - Yadav, Rajiv Kumar; Abhishek, Kumar; Mahapatra, Siba Sankar; Nandi, Goutam
Abstract: The Inconel alloy is enormously used as machined parts in the automobile and aerospace industries. The optimisation of machining parameters is imperative to strengthen the process performance outcomes concerning the quality and cost of the product. In general, machining is subjected to various process variables specifically feed (f), speed (S), depth of cut (t) and nose radius. The cutting force (Rf ), material removal rate (MRR), and surface roughness (Ra ) are relevant output performance indices. This paper evaluates the extent of process performance during the machining of Inconel 825 alloy. The development of a nonlinear regression model is done which articulates performance indices as a function of the aforementioned input variables. As a fitness function, the optimisation of the regression model is done employing the Rao1, Rao2, Rao3 JAYA and TLBO algorithm.